PEMBERDAYAAN POTENSI MASYARAKAT MELALUI PENDAMPINGAN USAHA MIKRO DAN KOPERASI DI DESA KARANGPANDAN REJOSO PASURUAN - Bambang Sutikno; Yufenti Oktafiah (Bajang Institute, 2023)
Empowerment of Micro Enterprises and Cooperatives plays an important and strategic role in supporting the success of the MSME and cooperative programs, especially in the economic businesses of MSME and cooperative actors so that the potential that exists in society can be optimized and developed in the world of entrepreneurship. Empowerment activities for good and professional micro and cooperative businesses will have a positive impact on the local economy in particular and at the same time the national economy. Empowerment through training and mentoring of micro and cooperative businesses is expected to be a reference for partners in doing entrepreneurship. Various efforts in the context of developing MSMEs and cooperatives have been carried out by various parties, including empowerment through training and mentoring, introducing approaches in the framework of MSME financing, cluster approach patterns and partnership patterns. The purpose of the empowerment service is to increase the knowledge of partners in preparing accounting reports, marketing and developing human resources through training and mentoring activities. This entrepreneurial empowerment activity was carried out from the 5th to the 7th of June 2023 which took place at the Karangpandan Rejoso Pasuruan Village Hall. Activities are carried out using lecture methods, discussions and applications from making simple bookkeeping reports according to Indonesian Accounting Standards, online marketing and utilizing local potential in entrepreneurial activities. The results of the pretest and posttest in empowerment activities show that from the answers to the questionnaire initially the partner is in the category of not understanding the importance of a financial report and a marketing model but after completing training and mentoring the partners answer with the same questions stating that they already understand and feel the many benefits gained in doing entrepreneurship in increasing partner business.